The dark side of social desire: Violence as metaphor, fantasy and satire in Argentina, 1969-1975 - Carassai, Sebastián Pablo (2015)
The 1970s was the most violent decade of the entire twentieth century for Argentina. Its first half was characterised by the rise of political radicalisation, and its second by the reign of state repression. Studies devoted to investigating the issue of violence in the 1970s have concentrated fundamentally on the protagonists. By contrast, this article offers an analysis of the symbolic terrain, shifting focus from the conscious to the unconscious plane, from the real to the imaginary world. Dealing with visual representations of violence in popular culture, especially advertising in mass-circulation magazines, it explores how violence became naturalised during the first half of the 1970s. In so doing it adds an additional layer to our understanding of the social mood that preceded the military coup of March 1976.